Diderot's counterpoints - Rex, W (Voltaire Foundation, 2017)
The exhilarating brilliance of Diderot’s ideas combined with the intractable difficulties we encounters in his writings place him among the most challenging and controversial of the philosophes. This book puts forward a clearer understanding of Diderot’s perplexities by taking into account the dynamics of his thought processes, especially the mode, peculiar to him, of thinking via contrarieties. Uniquely among the philosophes, Diderot has the irregular habit of letting his ideas capsize and go into reverse, ‘pro’ turning into ‘contra’, ‘yea’ becoming ‘nay’ – without the author bothering to notice (much less to inform the reader) that he has completely changed his mind. The phenomenon is frequent; in a number of instances, it is impossible to ‘make sense’ of Diderot’s writings unless we are alert to this even when it occurs, that is, alert the dynamics of contrariety. This feature of Diderot’s mental processes has received little attention from scholars – for good reasons: contrarieties suggest that the movement of Diderot’s thought is often neither logical nor even rational, that frequently his concepts do not remain fixed and stable, or add up along straight lines. The existence of contrarieties implies that, as Diderot wrote, his ideas proceed in discrete stages, creating an evolution of concepts whose values are not only changing, but often contradicting their previous meanings. Finally, contrarieties play against the principle, sacred to scholars of literature, that the ideas of work of art must have cogerence in order to be comprehensible. Accepting these challenges to tradition as the basis of his argument, Professor Rex proposes radically new analyses of almost all of Diderot’s major works (the only significant omission, La Religieuse, has been extensively treated by Professor Rex elsewhere). In sum, this perception of the dynamics of Diderot’s thought promises not only to alter fundamentally our understanding of his ‘philosophy’, but also to give a new sense of his importance in the Enlightenment. List of illustrations Acknowledgements Preface Introduction: he dynamics of Classical contrarieties I Contrariety in the Supplément de voyage de Bougainville II Evolving experiments in the Lettres sur les sourds et muets III The dubious fictions of the Entretiens sur le Fils naturel IV Stages of paradox in Le Paradoxe sur le comédien V The landscape demythologised: from Poussin’s serpents to Fénelon’s ‘shades’ and Diderot’s ghost VI Le Rêve de d’Alembert: Deus sive materia? VII Diderot against Greuze? VIII Stages of contrariety in Jacques le fataliste IX The dialectical dynamics of Le Neveu de Rameau Conclusion Index